Kajian Hukum Terhadap Efektifitas Perkuliahan di Tengah Pandemi Covid-19 - Daud Rismana; Hajar Salamah Salsabila Hariz; Fenny Bintarawati (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2022)
Law is a set of rules that exists in society to create order. Law is created by humans and for humans. As such, it should be able to humanize humans. Law must be present in the midst of any social circumstances, including once when Indonesia was hit by the COVID-19 pandemic. The emergence of the COVID-19 should be immediately addressed by issuing a policy to regulate lectures during the pandemic so that they can still run effectively as they should. This research implemented a descriptive qualitative method. Data and information related to the effectiveness of lectures in legal studies during the pandemic were collected. The data were then presented in words and analysed in a comprehensive description. The results show that the lectures during the pandemic had not been effective for many limitations experienced by students and lecturers. Furthermore, from a legal perspective, there are no clear rules/policies in regulating how lectures are conducted in the midst of the COVID-19 pandemic so that they can run effectively.